PERBANDINGAN RBL DAN PBL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK DI MAN 12 JAKARTA - Saputra, Aswin (Universitas Indraprasta PGRI, 2015)
Abstract: This study aims to determine differences in mathematics learning outcomes of students who use the RBL approach to PBL approach in MAN 12 Jakarta. The population in this study were 180 students of class X of MAN 12 Jakarta. Samples are 72 students, is determined by purposive sampling. Descriptive analysis revealed, that the mathematics learning outcomes of students who use the RBL approach gives the average (mean = 16.333) and mathematics learning outcomes of students who use the PBL approach gives the average (mean = 14.444). The results of correlation analysis showed mathematics learning outcomes of students who use the RBL approach provides a large contribution of 16% ( = 0.510; t = 2.994) than the outcome of learning mathematics learners using PBL approach. The results of the t test revealed a significant difference between the results of learning mathematics learners who use the RBL approach to mathematics learning outcomes of students who use the PBL approach. Thus, we can conclude that there are significant differences in mathematics learning outcomes of students who use the RBL approach rather than the result of learning mathematics learners using Problem Based Learning approach in MAN 12 Jakarta.Keyword: RBL, PBL, mathematics learning outcomes of students